Application of chromosome microarray analysis in patients with unexplained developmental delay/intellectual disability in South China - Rongyue Wang; Tingying Lei; Fang Fu; Ru Li; Xiangyi Jing; Xin Yang; Juan Liu; Dongzhi Li; Can Liao (Pediatrics and Neonatology)
Background and methods: Chromosome microarray analysis (CMA) is currently the first-tier diagnostic assay for the evaluation of developmental delay (DD) and intellectual disability (ID) with unknown etiology. Here, we present our clinical experience in implementing whole-genome high-resolution single nucleotide polymorphism (SNP) arrays to investigate 489 patients with unexplained DD/ID in whom standard karyotyping analyses showed normal karyotypes. This study aimed to assess the usefulness of CMA for clinical diagnostic testing in the Chinese population. Results: A total of 489 children were classified into three groups: isolated DD/ID (n = 358), DD/ID with epilepsy (n = 49), and DD/ID with other structural anomalies (n = 82). We identified 126 cases (25.8%, 126/489) of pathogenic copy number variants (CNVs) by CMA, including 89 (24.9%, 89/358) with isolated DD/ID, 13 (26.5%, 13/49) with DD/ID with epilepsy, and 24 (29.3%, 24/82) with DD/ID with other structural anomalies. Among the 126 cases of pathogenic CNVs, 79 cases were identified as microdeletion/microduplication syndromes, among which 76 cases were classified as common syndromes, and 3 cases were classified as rare syndromes, including 15q24 microdeletion syndrome, Xq28 microduplication syndrome and Lowe syndrome. Additionally, there were forty-seven cases of non-syndromic pathogenic CNVs. The ABAT, FTSJ1, DYNC1H1, and SETBP1 genes were identified as DD/ID candidate genes. Conclusion: Our findings suggest the necessity of CMA as a routine diagnostic test for unexplained DD/ID in South China. Key Words: developmental delay, intellectual disability, chromosome microarray analysis, CNVs, microdeletion/microduplication